2020
DOI: 10.1007/s11606-020-05853-8
|View full text |Cite
|
Sign up to set email alerts
|

Program Administrator Burnout in Graduate Medical Education: a Longitudinal Study

Abstract: BACKGROUND:Little is known about the level of burnout among program administrators (PAs) in medical education and its impact on the trainee environment. OBJECTIVE: To investigate variations in burnout levels over a 1-year period among a national cohort of PAs and examine any associations between perceived support and isolation. DESIGN: A 1-year longitudinal study conducted to assess burnout levels among PAs across the USA. The Copenhagen Burnout Inventory (score range, 0-100) was used to measure burnout over o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This was operationalized as the point at which additional data failed to generate new knowledge. Hence, the data provided a sufficient description of the phenomena explored (24). Therefore, we concluded that the data collection after twenty-one semi-structured interviews.…”
Section: Recruitment and Participantsmentioning
confidence: 89%
“…This was operationalized as the point at which additional data failed to generate new knowledge. Hence, the data provided a sufficient description of the phenomena explored (24). Therefore, we concluded that the data collection after twenty-one semi-structured interviews.…”
Section: Recruitment and Participantsmentioning
confidence: 89%